Sleep quality, quality of life, fatigue, and mental health in COVID-19 post-pandemic Türkiye: a cross-sectional study - Bener, Abdulbari; Morgul, Ebru; Tokaç, Mahmut; Ventriglio, Antonio; Jordan, Timothy R. (Frontiers in Public Health, 2024)
Aim: This study explores the predictors and associated risk factors of sleep quality, quality of life, fatigue, and mental health among the Turkish population, during the COVID-19 post-pandemic period.A cross-sectional survey using multi-stage, stratified random sampling was employed. In total, 3,200 persons were approached. Of these, 2,624 (82%) completed the questionnaire package consisting of socio-demographic information, Pittsburgh Sleep Quality Index (PSQI), WHOQOL-BREF, Fatigue Assessment Scale (FAS), Patients Health Questionnaire (PHQ-15), GAD-7 anxiety scale, and the 21-item Depression, Anxiety, Stress Scale (DASS-21).Results: Significant differences between genders were found regarding socio-demographics characters (p<0.01). Using PHQ-15 for depressive disorders, significant differences were found between normal and high severity scores (≥ 10), regarding age group (p<0.001), gender (p=0.049), educational level (p<0.001), occupational status (p=0.019), cigarette smoking (p=0.002), waterpipenarghile smoking (p=0.039), co-morbidity (p=0.003). The WHOQOL-BREF indicated strong correlations between public health, physical health, psychological status, social relationships, environmental conditions, and sleep disorders (p<0.01). Further, comparisons of the prevalence of mental health symptoms and sleeping with PHQ-15 scores ≥ 10 (p=0.039), fatigue (p=0.012), depression (p=0.009), anxiety (p=0.032), stress (p=0.045), and GAD-7 (p<0.001), were significantly higher amongst the mental health condition according to sleeping disorder status. Multiple regression analysis revealed that DASS21 stress (p<0.001), DASS21 depression (p<0.001), DASS21 anxiety (p=0.002), physical health (WHOQOL-BREF) (p=0.007), patient health depression-PHQ-15 (p=0.011), psychological health (WHOQOL-BREF) (p= 0.012), fatigue (p=0.017), and environmental factors (WHOQOL-BREF) (p=0.041) were the main predictor risk factors associated with sleep when adjusted for gender and age.The current study has shown that sleep quality was associated with the mental health symptoms of depression, anxiety, stress, and fatigue. In addition, Insufficient sleep duration and unsatisfactory sleep quality seemed to affect physical and mental health functioning.